Ultraviolet – C Dose Spread Simulation based on the Fixed-Lamp System in Universitas Multimedia Nusantara - Fahmy Rinanda Saputri; Niki Prastomo; Jeremy Pratama Wijaya (IJNMT (International Journal of New Media Technology), 2021)
Since Corona Virus Disease (COVID) – 19 is considered a pandemic by the World Health Organization (WHO), governments, and communities, worldwide trying to prevent transmission and reduce the number of deaths caused by the virus. One method of preventing transmission is spraying disinfectants using certain chemical compounds. However, chemicals can also hurt the environment and humans themselves if the doses used are not by existing standards. An alternative disinfectant method that does not use chemicals and is environmentally friendly, namely by using the UV (Ultraviolet)-decontamination method, UV-C rays. This research aims to find out the results of UV irradiation from UV-C lamps in theory and measurement. Then, the optimal placement of a fixed - UV lamp system to obtain an effective disinfectant dose and the length of time it takes to reach the target dose prevent the spread of the COVID-19 virus. The methods include theoretical calculations and data measurements to see the results of UV radiation irradiation on UV-C lamps and look for correlations between the two to find the conversion value. Moreover, with the help of DIALux Evo 9.2 software to find out the radiation value from the conversion equation, see the optimum UV dose spread, and reach the desired dose target time. The result is that there are differences in the results of UV irradiation on UV-C lamps with the efficiency of lamps and ballasts as well as on the measurement method that affects UV-C radiation, but according to field conditions and does not affect the actual application. The number of lamp placements and the dimensions of the room affects the dose spread. Moreover, the minimum time to achieve the target dose in the case study is 29 minutes using six placements of UV-C lamps with two lamps each at the six placement points.